Family Experience of Managing Emotions in Caring for People with Schizophrenia - Yulianto, Chiendo Daffa; Mubin, Mohammad Fatkhul; Novitasari, Andra (GLOBAL HEALTH SCIENCE GROUP, 2024)
Schizophrenia is a mental disorder that causes a person to lose their mind and disrupt interactions with others. Families caring for people with schizophrenia experience anxiety and confusion in caring for family members with schizophrenia. Families experience pressures such as economic burden, psychology, and negative societal stigma while caring for people with schizophrenia. These conditions will lead to changes in the expression of family emotions that can affect relapse in schizophrenics. Objective: This research aims to describe the family's experience of managing emotions in caring for people with schizophrenia. Method: This research uses a qualitative method with a phenomenological design. This research design was conducted with in-depth interviews. The research informants were family members of outpatient schizophrenia patients at RSJD Dr. Amino Gondohutomo Semarang, totaling 7 informants. The data analysis technique was carried out qualitatively based on the Miles & Huberman model. Results: Based on the results of in-depth interviews, 8 themes were obtained, namely feelings of sadness, feelings of disappointment, feelings of fear, worship, activities, social support, family communication, and healing of sufferer.This text outlines four main aspects of emotional expression in a group setting: negative emotional states, coping mechanisms, social environment, and caregiver behavior. Based on this theme, it is concluded that the importance of the social environment and communication in overcoming emotional problems, while overcoming parenting behavior can help reduce negative emotions in the family. Keywords: emotions; family; experiences; people with schizophrenia. Conclusions: The expression of family emotions found was a tendency towards the negative, namely feelings of sadness, feelings of disappointment, feelings of fear. The results of how to overcome family emotions found are social support, and family communication.